Fostering destination creativity through tourism lifestyle entrepreneurship: Exploring the moderating effect of financial orientation - Dias, Á.; Azambuja, T. (Creativity Studies, 2022)
The motivations and desires of tourists are constantly changing, and in this context, entrepreneurship demonstrates a significant contribution. Especially in the tourism industry, lifestyle entrepreneurs stand out for their contribution not only to the tourism sector, but also by their community attachment. Entrepreneurs with a lifestyle, goals, characteristics, and attitudes are distinct from other entrepreneurs. This research aims to portray the factors influencing their satisfaction with life perception, an important topic to understand their willingness to stay in the community. To this end, a survey was applied to 115 tourism lifestyle entrepreneurs, a data generated was analysed with partial least squares for confirmatory factor analysis. Findings reveal that networking, atmosphere, place attachment positively influence satisfaction with life. Furthermore, findings indicate that the financial objectives moderate these relationships, meaning that the way they conceive and act in their business also influences their satisfaction with life.